2011
DOI: 10.1002/j.1532-2149.2011.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of chronic neck pain: A prospective study among middle‐aged employees

Abstract: Objective: To study the associations of sociodemographic factors, working conditions, lifestyle and previous pain in the spine with new onset chronic neck pain (NP). Methods: The participants were municipal employees free of chronic NP at baseline, aged 40, 45, 50, 55 or 60 years (n = 5277, 80% women). Self-reported data on occupational class, working conditions, body mass index, smoking, exercise, mental well-being, sleep problems, NP and low back pain (LBP) were obtained from baseline questionnaire surveys i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
1
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 48 publications
6
53
1
11
Order By: Relevance
“…These two trajectories contained a considerable proportion (33%) of the study population, which is almost twice as high compared to previous studies on chronic NSP (12,13,17). Still, the occurrence of severe persistent NSP (9%) is in agreement with some studies using latent class growth modeling of NSP (17) and disabilities due to arm, neck, and shoulder complaints (23).…”
Section: Pain Trajectories and Occupational And Clinical Relevancesupporting
confidence: 85%
“…These two trajectories contained a considerable proportion (33%) of the study population, which is almost twice as high compared to previous studies on chronic NSP (12,13,17). Still, the occurrence of severe persistent NSP (9%) is in agreement with some studies using latent class growth modeling of NSP (17) and disabilities due to arm, neck, and shoulder complaints (23).…”
Section: Pain Trajectories and Occupational And Clinical Relevancesupporting
confidence: 85%
“…In our study, the main dimension observed was sensory, when compared with the affective dimension seen by Marques et al (26). Nevertheless, emotional factors such as work-related stress are risk factors for chronic neck pain, and the interference of pain in these aspects can be inferred by the words chosen in the affective category (30).…”
Section: Discussioncontrasting
confidence: 46%
“…Kääriä et al (2012) reported in their prospective cohort study among middle-aged (municipal) employees in Finland that the incidence of chronic neck pain was 15% in women and 9% in men 21) . For low back pain, Costa et al (2009) reported that 41.7% of patients with acute low back pain presenting to primary care in Australia developed chronicity 33) .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in incidence rates may be caused by methodological differences across studies, particularly in the definition of a symptomatic case and chronicity. Kääriä et al (2012) simply defined symptomatic cases as those having pain in the neck and chronic cases as those having pain that persisted for more than 3 months 21) . Costa et al (2009) defined symptomatic cases as those with pain lasting more than 24 hours but less than 2 weeks that was preceded by at least one pain-free month 33) .…”
Section: Discussionmentioning
confidence: 99%